Discussing the Patterns and the Outcomes of Populism in Southern Africa - Evaristus, Agberndifor (Advances in Social Sciences Research Journal, 2025)
And no wonder, for Satan himself masquerades as an angel of light. It is not surprising, then, if his servants also masquerade as servants of righteousness. Their end will be what their actions deserve (2 Corinthians 11:14-18) As per the scripture above, populism despite claiming to be the salvation of the country and for the masses is in all ways, the devil that appears as the angel of light but in effect has the intention and objective of deceiving the entire country. The deception stems from the fact that the agents of populism who are likened to the servants of the devil above, masquerade themselves as having the welfare of the country at heart and fighting for the good of the entire country. Alas, they are in the pursuit of personal glory, power, and aggrandizement. More so, they hold the sinister agenda of enslaving the entire country to maintain their grip in power. Lastly, regardless of their many promises, and show of good faith, populism by nature is no one’s friend but self and cares for no one but self.